Membangun Persekutuan Jemaat Seturut Efesus 4:1-16 di Stasi Santo Petrus Pematang Purba Saribudolog - Simanjuntak, M. Marihot; Saragih, Lestania Irawanni (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
This study aims to strengthen the community of believers at St. Peter's in Pematang Purba, St. Francis Assisi in Saribudolog, amidst its cultural and social diversity. This research employs the reader response method to investigate the church's understanding of biblical teachings and their application in daily life. The study reveals that humility, kindness, patience, and compassion demonstrated by church leaders and congregation members strengthen community cohesion. The congregation actively participates in church activities, though geographical challenges and shifting societal values impact face-to-face interactions. The study also highlights the importance of using technology as a tool for communication and community support. The novelty of this research lies in exploring how Christ's gifts are used to strengthen diverse communities and the impact of social changes and technology on interpersonal relationships. By combining biblical principles with practical contexts, this research provides a relevant model for other churches facing similar challenges. The findings of this study have the potential to strengthen the community and make significant contributions to the congregation of St. Peter's Station in Pematang Purba.